Microfluidic platform for serial mixing experiments with in operando nuclear magnetic resonance spectroscopy. Issue 8 (4th March 2021) - Plata, Marek; Hale, William; Sharma, Manvendra; Werner, Jörn M.; Utz, Marcel
Abstract : Coupling of pressure-driven microfuidics and NMR spectroscopy allows in operando observation of serial mixing experiments. Abstract : We present a microfluidic platform that allows in operando nuclear magnetic resonance (NMR) observation of serial mixing experiments. Gradually adding one reagent to another is a fundamental experimental modality, widely used to quantify equilibrium constants, for titrations, and in chemical kinetics studies. NMR provides a non-invasive means to quantify concentrations and to follow structural changes at the molecular level as a function of exchanged volume. Using active pneumatic valving on the microfluidic device directly inside an NMR spectrometer equipped with a transmission-line NMR microprobe, the system allows injection of aliquots and in situ mixing in a sample volume of less than 10 μL.